Carrageenans as heat stabilisers of white wine. (12th September 2019) - Ratnayake, S.; Stockdale, V.; Grafton, S.; Munro, P.; Robinson, A.L.; Pearson, W.; McRae, J.M.; Bacic, A.
Abstract: Background and Aims: Carrageenan addition has been previously shown to remove proteins from wine and to heat stabilise wines, however, many types of carrageenans are now available with potentially different protein‐adsorbing properties. This study investigated a range of commercially available carrageenans added at several stages of winemaking for efficacy of protein removal, heat stability and impact on wine sensory properties. Methods and Results: In preliminary screening trials, 11 types of carrageenan were added to a Chardonnay wine and the heat stability of the wine measured with a heat test. Three of the carrageenans successfully heat‐stabilised the wine and were included in large‐scale winemaking trials: sodium‐rich kappa ( k N), potassium‐rich kappa ( k K) and kappa / iota (90:10, ki ) carrageenan. Each carrageenan was added at three stages of winemaking, to juice, during fermentation and to wine. All carrageenans produced heat‐stable wine regardless of time of addition. Addition of k N during fermentation also improved wine recovery compared to bentonite addition, the positive Control, although sodium concentration also significantly increased in the wine. Addition of k K ‐ carrageenan to either wine or clarified juice was the most effective treatment for producing heat‐stable wine with minimal impact on the sensory profile, wine lees, turbidity and concentration of metal ions compared to that of untreated Control wines. Conclusions: Kappa ‐ and kappa ‐/ iota ‐carrageenans can be effective at heat stabilising white wines without negative impact on sensory properties, although the filterability and concentration of metal ions of the wines can vary with carrageenan structure and time of addition. Significance of the Study: Kappa ‐carrageenan, a renewable fining agent, is effective in heat stabilising wines and maybe become a useful alternative to bentonite.